Direct 2-Pyridyl-Alkylation of Benzyne with N-Alkylpyridinium Salts - Guo, Ning-Xin; Xia, Ji-Bao; Su, Yijin (Synthesis, 2023)
A 2-pyridyl-alkylation of benzyne using N-alkylpyridinium salts has been developed under either photochemical or thermal conditions. This metal-free dicarbofunctionalization of benzyne undergoes a de Mayo-type process including cascade dearomative [3+2] cycloaddition and rearomative ring-opening reaction. An electron-deficient N-cyclic alkyl group was necessary. A formal ortho-C–H arylation of pyridine has been achieved.
Keywords: benzyne; N-alkylpyridinium salts; dicarbofunctionalization; visible light; C–H arylation; de Mayo-type reaction